2015
DOI: 10.4073/csr.2015.20
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Improve the Labour Market Situation of Adults with Physical and/or Sensory Disabilities in Low‐ and Middle‐Income Countries: A Systematic Review

Abstract: The Campbell Collaboration (C2) was founded on the principle that systematic reviews on the effects of interventions will inform and help improve policy and services. C2 offers editorial and methodological support to review authors throughout the process of producing a systematic review. A number of C2's editors, librarians, methodologists and external peerreviewers contribute. The Campbell Collaboration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
2
21
0
Order By: Relevance
“…Thus, the level of difficulty someone has is partly dependent on the response of others around them. They are amongst the poorest and most disadvantaged people worldwide and substantially under-represented in formal and informal employment globally (Abidi & Sharma, 2014;Buckup, 2009;Mizunoya & Mitra, 2012;Tripney et al, 2015). Therefore, disability inclusion has become a compelling policy imperative in many countries.…”
Section: Some Foundational Concepts Relating To Disability Inclusive ...mentioning
confidence: 99%
“…Thus, the level of difficulty someone has is partly dependent on the response of others around them. They are amongst the poorest and most disadvantaged people worldwide and substantially under-represented in formal and informal employment globally (Abidi & Sharma, 2014;Buckup, 2009;Mizunoya & Mitra, 2012;Tripney et al, 2015). Therefore, disability inclusion has become a compelling policy imperative in many countries.…”
Section: Some Foundational Concepts Relating To Disability Inclusive ...mentioning
confidence: 99%
“… 35 Another high-quality review reported no difference in employment outcomes for people with any type of disability in a low income country participating in a multicomponent vocational intervention compared with those who did not receive this intervention (1 NRCT, 48 participants; RR not reported). 46 No further quantitative findings were described in these six reviews that altered the conclusions regarding the effectiveness of vocational intervention by health condition type reported above.…”
Section: Resultsmentioning
confidence: 98%
“…Full AMSTAR ratings are provided in online supplemental file, appendix E . Overall, we had high confidence in three reviews that focused on people with mental health conditions, 26 28 30 one review about people with traumatic brain injury, 27 and one review about people with any long-term health condition living in low-income to moderate-income countries, 46 but critically low to moderate confidence in the remainder of reviews. Common problems that reduced confidence in reviews included the lack of prepublished protocols, lack of transparency around how studies were selected and decisions to exclude studies, limitations in how risk of bias was evaluated and how this information was incorporated in the interpretation of review findings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Persons with disabilities in Low-and Middle-Income Countries (LMICs) have been marginalised, enduring a level of multipronged difficulties in all spheres of life that no other social group has encountered [1]. Existing evidence points to higher levels of poverty [2,3] and undernutrition [4], food insecurity and poor access [5], a worse health status [6], scarce access to healthcare and rehabilitation services [7,8], less availability of safe water and sanitation [9], a lower access to quality education [10][11][12][13], poor employment opportunities [14][15][16], and a higher risk of social and political exclusion [17][18][19]. As a result, meeting the sustainable development goals for persons with disabilities and the promotion of the "full and equal enjoyment of all human rights and fundamental freedoms" for persons with disabilities envisioned by the 2006 United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) in its article 1, require both the mainstreaming of disability in development initiatives and the mobilisation of extra resources to implement programs that can make a difference in LMICs [20].…”
Section: Introductionmentioning
confidence: 99%